1982
DOI: 10.1177/002199838201600603
|View full text |Cite
|
Sign up to set email alerts
|

Strength of Mechanically Fastened Composite Joints

Abstract: A method is presented for predicting the failure strength and failure mode of mechanically fastened fiber reinforced composite laminates. The method includes two steps. First, the stress distribution in the laminate is calculated by the use of a finite element method. Second, the failure load and the failure mode are predicted by means of a proposed failure hypothesis together with Yamada's failure criterion. A computer code was developed which can be used to calculate the maximum load and the mode of failure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
137
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 240 publications
(142 citation statements)
references
References 19 publications
0
137
0
2
Order By: Relevance
“…In reality, the effects of finite joint geometry, friction between the bolt and hole and bolt clamp-up can only really be treated rigorously within a finite element framework and most strength prediction methods are therefore based on FEA, either two-dimensional or (in a relatively limited number of studies) three-dimensional. Chang et al, [4] carried out a number of studies on composite bolted joints and applied the concept of the Whitney-Nuismer characteristic distances for open holes to strength prediction for a bolted joint. In formulating their model, they assumed a co-sinusoidal distribution of radial stress (from the bolt) on the inner surface of the hole and suggested that the characteristic distance (over which a failure criterion, in their case Yamada-Sun [5], has to be satisfied) varied from a critical tensile value at the location corresponding to net-tension failure to a critical compressive value at the location immediately beneath the bolt, corresponding to failure in bearing.…”
Section: Introductionmentioning
confidence: 99%
“…In reality, the effects of finite joint geometry, friction between the bolt and hole and bolt clamp-up can only really be treated rigorously within a finite element framework and most strength prediction methods are therefore based on FEA, either two-dimensional or (in a relatively limited number of studies) three-dimensional. Chang et al, [4] carried out a number of studies on composite bolted joints and applied the concept of the Whitney-Nuismer characteristic distances for open holes to strength prediction for a bolted joint. In formulating their model, they assumed a co-sinusoidal distribution of radial stress (from the bolt) on the inner surface of the hole and suggested that the characteristic distance (over which a failure criterion, in their case Yamada-Sun [5], has to be satisfied) varied from a critical tensile value at the location corresponding to net-tension failure to a critical compressive value at the location immediately beneath the bolt, corresponding to failure in bearing.…”
Section: Introductionmentioning
confidence: 99%
“…[5]. Within these twodimensional approaches, however, there are some very useful models which provide a framework for predicting damage initiation and growth -for example the Damage Zone Model developed by Hollmann [6].…”
Section: Introductionmentioning
confidence: 99%
“…In the average stress model, it is assumed that final failure occurs when the laminate stress averaged over a characteristic distance is equal to the unnotched strength of the laminate. Modifications of the point stress and average stress models using ply strengths have been proposed to predict the strength of laminates with open and loaded holes [17]- [18]. The advantage of using ply properties rather than laminate properties is that the need to measure laminate strengths for every layup is avoided.…”
Section: Introductionmentioning
confidence: 99%